State Debt in the Post-crisis Period: Realities and Prospects Государственный долг в посткризисном периоде: реалии и перспективы - Bets Oleksandr I. (Bìznes Inform, 2013)
The goal of the article is clarification of the debt problems during the post-crisis period. Irrational debt policy based on considerations of the moment during the crisis and post-crisis periods formed risks of violation of the macro-financial stability in the country. This results in a number of negative tendencies, reduces fiscal environment and forms limitations for restoration of the state economy during the post-crisis period. Results of theoretical and empirical studies testify to the fact that the high state debt negatively influences the rates of economic growth under the influence of the following factors: de-stimulation of private investments, risks of default and financial destabilisation, increase of real interest rates, growth of vulnerability to the impact of external shocks, increase of macro-economic uncertainty and increase of default probability. It is expedient to continue the study of fiscal and budget policy and mechanisms of ensuring the debt stability of the countries with the aim to ensure restoration of economies during the post-crisis period. Целью публикации является освещение долговой проблематики в посткризисном периоде. Нерациональная и конъюнктурная долговая политика в кризисный и посткризисный периоды сформировала риски нарушения макрофинансовой стабильности в стране. Это обусловливает ряд негативных тенденций, сокращает фискальное пространство и формирует ограничения для восстановления экономики государства в посткризисный период. Результаты теоретических и эмпирических исследований свидетельствуют о том, что высокий государственный долг негативно влияет на темпы экономического роста под влиянием следующих факторов: дестимулирование частных инвестиций – риски дефолта и финансовой дестабилизации, повышение реальных процентных ставок, рост уязвимости к воздействию внешних шоков, усиление макроэкономической неопределенности и повышение вероятности дефолта. В дальнейшем целесообразно продолжить исследования фискально-бюджетной политики и механизмов обеспечения долговой устойчивости стран с целью обеспечения восстановления экономик в поскризисный период.